An Allosteric Inhibitory Potential of Triterpenes from Combretum racemosum on the Structural and Functional Dynamics of Plasmodium falciparum Lactate Dehydrogenase Binding Landscape. Issue 2 (4th January 2022) - Oluyemi, Wande M.; Samuel, Babatunde B.; Adewumi, Adeniyi T.; Adekunle, Yemi A.; Soliman, Mahmoud E. S.; Krenn, Liselotte
Abstract: Multidrug resistance is a significant drawback in malaria treatment, and mutations in the active sites of the many critical antimalarial drug targets have remained challenging. Therefore, this has necessitated the global search for new drugs with new mechanisms of action. Plasmodium falciparum lactate dehydrogenase ( pf LHD), a glycolytic enzyme, has emerged as a potential target for developing new drugs due to the parasite reliance on glycolysis for energy. Strong substrate‐binding is required in pf LDH enzymatic catalysis; however, there is a lack of information on small molecules' inhibitory mechanism bound to the substrate‐binding pocket. Therefore, this study investigated a potential allosteric inhibition of pf LDH by targeting the substrate‐binding site. The structural and functional behaviour of madecassic acid (MA), the most promising among the six triterpenes bound to pf LDH, were unravelled using molecular dynamic simulations at 300 ns to gain insights into its mechanism of binding and inhibition and chloroquine as a standard drug. The docking studies identified that the substrate site has the preferred position for the compounds even in the absence of a co‐factor. The bound ligands showed comparably higher binding affinity at the substrate site than at the co‐factor site. Mechanistically, a characteristic loop implicated in the enzyme catalytic activity was identified at the substrate site. This loop accommodates key interacting residues (LYS174, MET175, LEU177 and LYS179) pivotal in the MA binding and inhibitory action. The MA‐bound pf LHD average RMSD (1.60 Å) relative to chloroquine‐bound pf LHD RMSD (2.00 Å) showed higher stability for the substrate pocket, explaining the higher binding affinity (−33.40 kcal/mol) observed in the energy calculations, indicating that MA exhibited profound inhibitory activity. The significant pf LDH loop conformational changes and the allostery substrate‐binding landscape suggested inhibiting the enzyme function, which provides an avenue for designing antimalarial compounds in the future studies of pf LDH protein as a target. Abstract :